someone please solve it fast.
Attachments:
![](https://hi-static.z-dn.net/files/d09/49404c4f85d3b96e90411d48e398657f.jpg)
Answers
Answered by
0
LHS= [cosecA/ cosecA-1] + [cosecA/ cosecA+1]
= cosecA( cosecA+ 1) + cosecA( cosecA- 1)/ cosec^2A- 1
= cosecA( cosecA+ 1 + cosecA - 1)/ cot^2A
=2cosec^2A/ cot^2A
=(2/sin^2A)/(cos^2A/ sin^2A)
= 2/cos^2A
=2sec^2A= RHS
hence proved
= cosecA( cosecA+ 1) + cosecA( cosecA- 1)/ cosec^2A- 1
= cosecA( cosecA+ 1 + cosecA - 1)/ cot^2A
=2cosec^2A/ cot^2A
=(2/sin^2A)/(cos^2A/ sin^2A)
= 2/cos^2A
=2sec^2A= RHS
hence proved
Similar questions